Date Palm Byproducts: A Sustainable Material base for the Future Bioeconomy (London Journal of Engineering Research, 2023)
The date palm byproducts result from the annual pruning of date palms (e.g. leaves or fronds, petioles, empty fruit bunches, spathes, leaf sheaths fibers), processes of renewal of date palm plantations (date palm trunks), as well as sorting and manufacture of dates (date kernels and date wastes). Unfortunately these byproducts are most dominantly treated as waste, being either open-field burnt resulting in tremendous environmental pollution, or dumped in landfills. This results into heavy environmental pollution and inflicts huge economic losses. Meanwhile, these date palm byproducts can be considered as a sustainable feedstock of renewable materials that can serve as a sustainable material base for a wide spectrum of industries to satisfy human needs and as a springboard for circular bioeconomy.
Keywords: tumor; therapy; lactate; Warburg effect; frequencies; electromagneticpectrum; bandwidth; signal; magnetic field; powers.